Crossroads of rural crime : representations and realities of transgression in the Australian countryside - Harkness, Alistair; White, R. D. 1956- (Emerald Publishing Limited, 2021)
Rural-oriented scholarship in criminology is growing, in part motivated by governmental, community and academic recognition that, despite stereotypes of the 'rural idyll', crime and justice are significant issues in the rural landscape. Using the notion of 'crossroads' to provide a unique lens through which to examine realities of rural crime, Crossroads of Rural Crime: Representations and Realities of Transgression in the Australian Countryside provides a dynamic understanding of the nature of rural life and ways in which transgression manifests itself in the context of a presumed rural-urban divide. Common myths regarding rural crime are challenged by exploring its diverse dimensions from a central conceptual focal point; the many 'roads' that lead into and out of rural spaces, whether literal, virtual or figurative. With a focus on the Australian countryside, the authors examine issues such as drug abuse, persecution of wildlife, rural penal practices, and health in Indigenous communities. The first substantive edited collection to focus on notions of the mobility of crime within, to and from rural spaces, this interdisciplinary collection draws together contributions from criminology, politics, sociology, Indigenous studies, literature and anthropology to significantly contribute to our understanding of rural crime.